EEG Characteristics to Hyperventilation by Age and Sex in Patients With Various Neurological Disorders - Khachidze, Irma; Gugushvili, Manana; Advadze, Maia (Frontiers in Neurology, 2021)
Introduction: Hyperventilation provocation tests (HPT) have been applied in patients for the detection of hidden disorders of the nervous system (CNS), especially the pathological forms of Central NS. HPT is relevant and valuable for the study of electroencephalography (EEG). The various types of abnormal EEG responses to HPT provoke different interpretations, while the research of these phenomena is still subject to investigation. Nowadays is a lack of data and no systemic analysis according to onset time on pathological EEG responses to hyperventilation (PERH) in humans, especially concerning their age and biological sex. Methods: The EEG of 985 outpatients with various functional disorders of the CNS was examined. In our previous studies were detected three types of PERH (disorganization of basic rhythm, paroxysmal discharges, and epileptiform activity) according to the time of manifestation (first, second, third minutes). The current work was aimed to classify PERH, take into account the age (3-6, 7-12, 13-18, 19-30, 31-50, 50<), and biological sex (mail. female) of the patients. Results: The disorganization of basic EEG rhythm in the first, second and third minutes of HPT shown in all age and sex groups. All three types of PERH in the first minute were revealed in all sex, which was not observed in the second and third minutes. All three types of PERH in the first and the second minutes were found only in women. The second type of PERH has revealed at the second minute of PHT in 13-18-year-old girls. Conclusion: The three main types of PERH were detected at the first minute in all ages and sex of patients with various CNS dysfunctions. This is diagnostically informative should be used as a marker during the monitoring of treatment. The specificity activity of the brain response to HPT depending on time, age, sex. The data will serve as a reminder that accounting for sex differences and ages during HPT leads to better results. The sensitivity and severity of the NS reaction towards hypocapnia, stress, emotion increase during puberty, particularly in 13-18-year women. Therefore, in such cases should not be recommended to expand functional loads.